Immigration Influx as a Trigger for Right-Wing Crime: a Temporal Analysis of Hate Crimes in Germany in the Light of the ‘Refugee Crisis' - Piatkowska, Sylwia J. (The British journal of criminology, 2020)
This study examines the conditions under which increased immigration rates serve as a catalyst for right-wing politically motivated crime across 16 German regions. The main objective is to focus on regional immigration rates as a potential trigger for threat perceptions by not only testing their principal effects but also by considering their interactions with structural environments. The analyses are grounded in a quasi-experimental setting because Germany recently witnessed an increase in immigration, publicly referred to as the ‘refugee crisis'. The results reveal differences in the comparable models, insofar as high regional immigration rates are particularly associated with hate crimes during times of high immigration influx, illustrating how a signal event such as the ‘refugee crisis' might trigger amplified threat perceptions.